An RNase-sensitive particle containing Drosophila melanogaster DNA topoisomerase II (The Rockefeller University Press, 1994)
Most DNA topoisomerase II (topo II) in cell-free extracts of 0-2-h old Drosophila embryos appears to be nonnuclear and remains in the supernatant after low-speed centrifugation (10,000 g). Virtually all of this apparently soluble topo II is particulate with a sedimentation coefficient of 67 S. Similar topo II-containing particles were detected in Drosophila Kc tissue culture cells, 16-19-h old embryos and extracts of progesterone-matured oocytes from Xenopus. Drosophila topo II- containing particles were insensitive to EDTA, Triton X-100 and DNase I, but could be disrupted by incubation with 0.3 M NaCl or RNase A. After either disruptive treatment, topo II sedimented at 9 S. topo II- containing particles were also sensitive to micrococcal nuclease. Results of chemical cross-linking corroborated those obtained by centrifugation. Immunoblot analyses demonstrated that topo II- containing particles lacked significant amounts of lamin, nuclear pore complex protein gp210, proliferating cell nuclear antigen, RNA polymerase II subunits, histones, coilin, and nucleolin. Northern blot analyses demonstrated that topo II-containing particles lacked U RNA. Thus, current data support the notion that nonnuclear Drosophila topo II-containing particles are composed largely of topo II and an unknown RNA molecule(s).